Fighting terrorism and extremism in the Russian Federation and worldwide: common issues - Kniazeva E.A., Korobeev A.I.,Kuchina Y.O., Kniazeva N.A., (Opción, 2019)
This article is dedicated to the issues that the Russian Federation faces during its anti-terrorism prevention and policy development with a focus on three aspects - the specifics of criminological manifestations of terrorism and extremism in Russia, their links with international trends in this field and the problems faced by the state on the way to counteract these negative phenomena. The basis for this article is the research conducted by us in the framework of research to counter terrorism and extremism in the Far Eastern Federal University, in the field of national, comparative and international law.